Rancang Bangun Aplikasi Thermovision Untuk Pemetaan Distribusi Suhu Dan Permulaan Penyalaan Magnesium Pada Pembubutan Kecepatan Tinggi - Mahrudi, Haris; Burhanuddin, Yanuar (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
Objective of this research is making thermovision application for heat mapping. The research is carried out with machining magnesium which chisel holder is designed with a thermocouple on the tip of it. The thermocouple is used as parameter to the maximum and also minimum temperature of the application. The machining process is done at the same time when the video is recorded. After the filming process, the video will be converted into several images (.Jpg format). The images will then be processed by using the thermovision application. After the images are loaded in the application, the distribution of temperature can be seen based on several areas of colors. The result of some image reading by using the thermovision application shows that temperature distribution happens through colors and it also shows the number of temperature in Celsius degree calculation. As seen in the image capturing of object with a range of temperature for about 100°C-150°C, a maximum temperature that can be obtained is 145.662°C and the minimum temperature is 120.973°C. This range of temperature is not too far from the maximum and minimum temperature of the thermocouple.Keywords: magnesium material, distribution of temperature, thermovision application.